Persepsi Siswa terhadap Keterampilan Berkomunikasi Guru dalam Pembelajaran di SMK Negeri 9 Padang - Arsela, Maria; Syahril, Syahril (ARZUSIN, 2023)
This research is based on the results of observations made by the author during observations at SMK N 9 Padang, from the observations made it appears that there are still teachers who have poor communication skills in learning. This research aims to obtain data and information regarding how good the communication skills of teachers at SMK N 9 Padang are in learning according to students' perceptions seen from several aspects: 1) conveying messages orally, 2) conveying messages in writing, and 3) receiving messages. Therefore, the problem that will be studied in this research is, "How good are the communication skills of SMK N 9 Padang teachers in learning according to students' perceptions". This research is a quantitative descriptive study with a research population of 1268 students and the sample size was determined using the Slovin formula with an error rate of 10% with the Proportionate Stratified Random Sampling technique obtaining 95 students as the research sample. The instrument used in this research was a questionnaire with a Liker scale model. From the results of data processing, teachers' communication skills in learning when conveying messages orally obtained an average score of 3.6 in the good category, for teachers' communication skills in learning when conveying messages in writing, they obtained an average score of 3.4, which was in the quite good category. , and for teachers' communication skills in learning when receiving messages, they obtained an average score of 3.5 in the quite good category. Overall it can be concluded that the teacher's communication skills in learning at SMK N 9 Padang are in the quite good category.